2021
DOI: 10.3390/antibiotics10060713
|View full text |Cite
|
Sign up to set email alerts
|

Bee Pollen and Bee Bread as a Source of Bacteria Producing Antimicrobials

Abstract: The principal objective of the study was the isolation and identification of bacteria that are present in mature bee bread (BB) and dried (ready for selling and consumption) bee pollen (BP). Obtained isolates were screened for their potential to inhibit select human pathogenic bacteria and their ability to produce enzymes of particular industrial importance. Four and five samples of BP and BB, respectively, were used for the study. In total, 81 strains of bacteria were isolated, and 34 (42%) of them exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 47 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…It provides easily digestible carbohydrates, proteins, fats, minerals, and vitamins for the bee larvae and the adult bees, but also acts as a functional food (feed), possessing antioxidant and anti-inflammatory properties [1][2][3]. Even though many studies in the last years have been focused on the bacterial composition of bee bread [4][5][6], those on fungal composition are rather scarce despite the publication of some of them dating from the '80s [7]. An exception is the study of Tauber et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…It provides easily digestible carbohydrates, proteins, fats, minerals, and vitamins for the bee larvae and the adult bees, but also acts as a functional food (feed), possessing antioxidant and anti-inflammatory properties [1][2][3]. Even though many studies in the last years have been focused on the bacterial composition of bee bread [4][5][6], those on fungal composition are rather scarce despite the publication of some of them dating from the '80s [7]. An exception is the study of Tauber et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…The sample BP5, which had the highest contents of polyphenols and flavonoids, but also of individual polyphenols, generally had the best antimicrobial effect, which indicates a link between the presence of these compounds and the improved antimicrobial action; this finding is also supported by other authors [ 35 ]. Pełka et al [ 89 ] found higher antimicrobial potential in natural FBP compared to BP. Bee bread extracts showed inhibitory potential against S. aureus strains, while some pollen extracts lacked efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, several polish BB samples exerted higher inhibitory potential against Staphylococcus aureus ATCC 25923 and ATCC 29213. Furthermore, several pieces effectively inhibited the growth of S. aureus and MRSA (methicillin-resistant S. aureus ), strains at concentrations between 2.5 and 5.0% ( 179 ). In the following study, the bacterial isolates of mature BB exhibited moderate antagonistic effects against S. aureus ATCC 25923, ATCC 29213, S. epidermidis ATCC 12228, P. aeruginosa ATCC 27853, and lower results against Escherichia coli ATCC 25922 ( 180 ).…”
Section: Potential Therapeutic Properties Of Labs Found In Bb And/or ...mentioning
confidence: 99%